Balancing participation in writing meeting minutes online in video-mediated return-to-work negotiations - Weiste, Elina; Koskela, Inka; Kallio, Aku; Keränen, Hanna; Pesonen, Sanna; Sormunen, Erja; Juvonen-Posti, Pirjo; Ruusuvuori, Johanna (Frontiers in Communication, 2023)
Balancing participation in multiparty negotiations in healthcare and vocational rehabilitation processes is an interactional challenge, especially when the participants interact online. Participants in multiparty video-mediated context have limited and asymmetric access to each other’s activities. Also the different meeting tasks cause an imbalance in their opportunities to participate. At the same time, contemporary clinical practice rests on the ideal of reciprocal, balanced participation. In this study, we used conversation analysis to examine the participants’ construction of the meeting memo as a joint document in video-mediated return-to-work negotiations. We aim to observe how participants views are invited, receipted, and jointly formulated, both verbally and writing, when constructing the meeting memo. These negotiations are common collaboration arenas of vocational rehabilitation in Finland which aim to support the employee’s return to work, for instance, after sickness absence. The meeting memo is a summary of the negotiation and its concrete decisions which may affect the employee’s disability-based vocational rehabilitation services and benefits. Our results indicate that the way in which the meeting memo is produced in RTW negotiations plays a significant role in the participants’ opportunities for participation. Sharing the screen view to the already written text, enable participants to comment on and correct the text, reinforcing its joint approval. Involvement of participants in co-producing memo texts allow the participants not only produce the content to the text but also to formulate the publicly available form of the text. These practices for constructing the memo in and through the unfolding of interaction may be considered as enhancing more balanced participation. However, they may also require extra interactional effort in multiparty video-mediated negotiations.